2008
DOI: 10.1007/s00167-008-0509-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported activity level and knee function in amateur football players: the influence of age, gender, history of knee injury and level of competition

Abstract: OBJECTIVE:To investigate if self-reported activity level or knee function are influenced by subject characteristics, level of competition and history of knee injury. DESIGN:Cross-Sectional study using questionnaires distributed at a personal visit.PARTICIPANTS: 188 (65 women) amateur football players in 10 football clubs from each division below national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
53
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 31 publications
11
53
0
2
Order By: Relevance
“…This finding is in accordance with previous studies 12,13,17 in which similar functional outcomes were seen in patients with higher BMI scores after ACLR. Overall, we observed that a higher BMI was associated with lower subjective IKDC scores at 1 and 2 months, but this effect did not necessarily occur when the traditional obesity threshold was used as a cutoff point (nonobese ¼ BMI ,30, obese ¼ BMI !30).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in accordance with previous studies 12,13,17 in which similar functional outcomes were seen in patients with higher BMI scores after ACLR. Overall, we observed that a higher BMI was associated with lower subjective IKDC scores at 1 and 2 months, but this effect did not necessarily occur when the traditional obesity threshold was used as a cutoff point (nonobese ¼ BMI ,30, obese ¼ BMI !30).…”
Section: Discussionsupporting
confidence: 93%
“…5,[14][15][16][17][18][19][20] In particular, medial meniscectomy, residual ligamentous laxity, and femoral chondral defects have all been associated with subsequent degenerative arthrosis as seen on radiography. 5,15,20 Studies also suggest that demographic risk factors such as age, sex, and body mass index (BMI) might have a profound influence on self-reported outcomes after ACLR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The other KOOS subscale scores reported by ACL-deficient groups were similar to those reported by the general Swedish population (Frobell et al, 2008). In contrast, all ACL-deficient groups reported more knee pain and worse function in sport and recreation compared to amateur soccer players and military …”
Section: Comparison To Normative Populationssupporting
confidence: 75%
“…KOOS-QOL scores in ACL-deficient individuals ranged from 54 ± 17 (Lohmander et al, 2004) to 77 ± 22 (Swirtun & Renström, 2008) (mean ± SD), these were impaired compared to Swedish general population norms (81 ± 24) (Paradowski et al, 2006), Swedish amateur soccer players with minor (14%), severe (23%) or no history (63%) of knee injury (88 ± 17) (Frobell, Svensson, Gothrick, & Roos, 2008) and a population of military recruits (92 ± 28) (Cameron et al, 2013). The other KOOS subscale scores reported by ACL-deficient groups were similar to those reported by the general Swedish population (Frobell et al, 2008).…”
Section: Comparison To Normative Populationsmentioning
confidence: 92%